Management strategies for organisational implementation of systemic change: A qualitative analysis - Ghavifekr, S.; Afshari, M.; Ayoufu, W. (2012)
In the current environment of market competition and globalization, change management strategies become increasingly important for all organizations including education. In this regard, managing systemic change implementation has been considered as the integral part of the change process to achieve organizational desired goals and objectives. For educational organizations, especially Open and Distance Learning (ODL) institutions, management strategic planning for technological change implementation are believed to be the key solution to improve the quality of teaching and learning process. This paper aims to address the key question of “What are the management strategies and policies for effective organizational implementation of the systemic change in context of an ODL organization?” Based on the data analysis for this qualitative research it was found that in a technologybased systemic change, planning, organizing, guiding and monitoring are the main strategic elements for the management in successful organizational implementation of the new learning technologies. “Organizational implementation” as one of the key components of systemic change management is the main theme for this study. The results of in-depth analysis including emerged sub-themes and the subsub- themes are presented in this paper.